Hydrogen nitrogening in great discharge with AC power - Stechyshyna, N.M.; Stechyshyn, M.S.; Martynyuk, A.V.; Gladkiy, Ya.M. (Problems of Tribology, 2021)
The paper substantiates and experimentally shows the possibility of anhydrous nitriding in a glow discharge (BATR) with AC power supply (AC), as well as the possibility of switching the shape of pulses, changing their polarity, which is solved by introducing a glow discharge nitriding device with a power source alternating current of a given frequency. The analysis of the results of metallographic studies of the modified layer indicated the presence of a more uniform gradient of hardness in depth (gradient decreased by 1.7 - 3.5 times), which increases the wear resistance of parts and quality indicators of strengthening parts while reducing processing costs and installation costs. At BATR in CCR with supply of current of industrial frequency the installation for realization of process becomes cheaper. The latter factor will contribute, among other aspects, to the wider introduction of BATR technologies. The use of alternating current affects the course and results of nitriding, as periodic changes in the polarity of the electrodes of the chamber contributes to the cleaning of the surface from the adsorption layer, which positively affects the nature of nitrogen saturation (gradient of microhardness times), contributes to a significant change in the phase composition of the surface modified layer and allows to expand the technological capabilities of nitriding in the direction of obtaining the required performance characteristics of working surfaces, in particular tribological characteristics